2008
DOI: 10.1111/j.1439-0264.2008.00878.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Bone Histology of Adult Horses (Equus caballus) and Cows (Bos taurus)

Abstract: Bone microstructure of domestic herbivores is still not completely understood. Indeed, works focused on the bone histology of numerous Mammalian species frequently led to misunderstandings because of the high number of variations such as the kind of bone, section orientation, species, breed and age. Moreover, attempts to identify the species in archaeozoological studies by a mere qualitative approach have not been encouraging and in recent years quantitative methods, based on image processing and statistical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
29
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 17 publications
6
29
0
Order By: Relevance
“…Haversian bone, with a number of primary vascular canals, and primary and secondary osteons [20,25,39]. Some of the secondary osteons were often linearly arranged in bands similar to observations by Cuijpers [20].…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…Haversian bone, with a number of primary vascular canals, and primary and secondary osteons [20,25,39]. Some of the secondary osteons were often linearly arranged in bands similar to observations by Cuijpers [20].…”
Section: Discussionsupporting
confidence: 67%
“…Also, unlike reports by Martiniaková et al [18,21,22] sheep femora did not comprise of plexiform bone but rather of primary vascular longitudinal bone with a number of primary osteons. This dissimilarity can also be ascribed to the differences associated with various breeds of sheep utilised in the several studies [26,39]. To the knowledge of the authors this is the first study to describe the histological arrangement of impala femora and a number of histomorphological similarities between impala and sheep femora were reported.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…From the mechanics point of view, modelling results demonstrated a significant impact of material properties of cement lines on microcrack-osteon interactions [74,99]. Quantitative analyses of cortical bone have also reported that the size and density of osteons vary with age [78,[100][101][102][103][104]. Because cement lines are prime sites for microcrack formation, an increase in the osteon density could lead to a higher microcrack density, which could reduce the crack-initiation toughness [32,34].…”
Section: Bone Toughening Mechanismsmentioning
confidence: 99%